WOMEN’S ENTREPRENEURSHIP AND DIGITAL INNOVATION IN TRADITIONAL MARKET: INSIGHTS FROM BERINGHARJO, YOGYAKARTA - Indriawati, Ratna Malisa; Ainina Ratnadewati; Anisya Nur Widya (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
This paper examines the impact of digital economy tools on the business performance and empowerment of women entrepreneurs in Beringharjo Market, Yogyakarta. It focuses on how digital bookkeeping, e-commerce, social media advertising, and digital payment systems influence monthly turnover. This research uniquely focuses on women entrepreneurs in a traditional Indonesian market, combining localized data with digital economy analysis. Using a quantitative approach, the study surveyed 143 women entrepreneurs in Beringharjo Market. It employed Ordinary Least Squares (OLS) regression to analyze the relationship between turnover and four independent variables: digital bookkeeping, e-commerce usage, social media advertising, and digital payment adoption. Digital bookkeeping has the most statistically significant impact on turnover. The results suggest that financial management tools are most effective, while marketing tools offer potential benefits, and payment tools serve more operational roles. Digital payments improve efficiency but do not directly boost revenue. The study supports the advancement of SDG 5 (Gender Equality) and SDG 8 (Decent Work and Economic Growth), recommending digital literacy programs, improved tech access, and supportive policies to maximize impact.